ON THE CONTINUITY OF EXTREMAL LENGTH - Navoyan, Kh.V.; Navoyan, V.Kh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2013)
In the paper the continuity of one conformal invariant extremal length is considered. A counterexample is constructed disproving the result of P.M. Tamrazov on the continuity of the extremal distance between two sets. Then some sufficient conditions for the continuity are given.
Keywords: extremal length; module of curve family; separated compact subset